増殖分化因子１５（ＧＤＦ−１５）を使用して代謝障害を処置するまたは軽快させる方法 (2021)
The disclosure relates to the treatment of non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH), as well as end-stage liver disease, hepatic steatosis (fatty liver), liver fibrosis, liver inflammation, liver cirrhosis, primary biliary cirrhosis (PBC), and hepatocellular carcinoma (HCC), by administering to a subject in need a GDF15 protein or a functional variant, mutation, fusion, or conjugate thereof, and to pharmaceutical compositions that contain the same.